Perancangan Dan Penyusunan Sistem Akuntansi Berbasis Microsoft Access Pada Toko Batam Filterindo - Serly Serly; Fanny Desmita Liyanti (ConCEPt - Conference on Community Engagement Project, 2021)
Toko Batam Filterindo is a business that is engaged in trading of sparepart for drinking water. Toko Batam Filterindo still does not have an accurate accounting recording system. The purpose of this work is hope that a system that has been designed by the author based on microsoft access can produce accurate financial reports and help make it easier for shop owners to record daily transactions. Therefore, the first thing the author did was to find the problems faced by shop owners and provide the right solutions to the shop owners. The method of implementation applied by the author in this work is training. The author conducts training for owners and employees on how to access the system that has been designed from the main page to how to monitor the financial reports available in the system. The output achieved in this work is designing accounting recording system based on microsoft access, in this system it can produce financial position reports, income statements, changes in equity reports, cash flow reports, inventory reports, general ledgers, and general journals. In addition to designing an accounting recording system, the author arrange guidebook to make it easier for owners in the process of using the system. The accounting recording system designed by the author hopes to improve the recording system at the Toko Batam Filteridno. Recommendations for future are designing a system that contains accounts payable reports, asset reports, tax reports and other reports that have not been designed in this system.